1986
DOI: 10.1021/bi00370a027
|View full text |Cite
|
Sign up to set email alerts
|

Model of fibronectin tertiary structure based on studies of interactions between fragments

Abstract: Human plasma fibronectin aggregates in solution and is thought to form fibrils on cell surfaces, perhaps by self-associating and by interacting with other components such as proteoglycans. We have localized the self-association domains by testing the ability of various fragments of fibronectin to interact with each other. Complexation between fluorescamine-labeled fragments and unlabeled fragments or whole molecules was assessed by gel filtration high-performance liquid chromatography. The fragments studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 59 publications
2
63
0
Order By: Relevance
“…Therefore, throughout this review the term Fn-f will be used generically. The typical Fn-fs studied by us are generated by sequential cathepsin D and thrombin digestion of human plasma Fn (56,60,61) and are active on bovine (56), human knee (62,65), rabbit and rat cartilage explant cultures (unpublished). Similar cathepsin D and thrombin generated Fn-fs from rabbit plasma Fn, bovine plasma Fn, rat plasma Fn or guinea pig plasma Fn are equally active on bovine cartilage (unpublished).…”
Section: Fn-fs Enhance Loss Of Pg From Cartilage Explantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, throughout this review the term Fn-f will be used generically. The typical Fn-fs studied by us are generated by sequential cathepsin D and thrombin digestion of human plasma Fn (56,60,61) and are active on bovine (56), human knee (62,65), rabbit and rat cartilage explant cultures (unpublished). Similar cathepsin D and thrombin generated Fn-fs from rabbit plasma Fn, bovine plasma Fn, rat plasma Fn or guinea pig plasma Fn are equally active on bovine cartilage (unpublished).…”
Section: Fn-fs Enhance Loss Of Pg From Cartilage Explantsmentioning
confidence: 99%
“…In this model, the fibrils are initially formed through domain to domain interactions involving the interaction of the domains of the most potent chondrolytic Fn-f, the 29-kDa Fn-f, with domains of Fn having the type III homology structures found in the 140-kDa cell-binding Fn-f. We reported years ago that the 29-kDa aminoterminal Fn-f interacted with the 140-kDa Fn-f in polymerization reactions (60,121,122).…”
Section: The Fn-fs May Act Through the Alpha 5 Beta 1 Rgdsdependent Fmentioning
confidence: 99%
“…Their formation at sites of injury is thought to result from regulated protease activity [4,19,20]. Proteases are certainly required for wound repair and the formation of fibronectin fragments may optimize such processes by initiating biological responses that can be quite different from those expressed by the intact fibronectin molecule [7,[21][22][23][24]. We recently reported that intact fibronectin and two gelatin-binding fibronectin fragments supported in vitro interaction between soluble 125 I-radiolabeled gelatin and macrophages [1].…”
Section: Introductionmentioning
confidence: 99%
“…We suggest a new model made from the distribution over a sphere of compact domains arranged in a way discussed by Homandberg et al [35]. This model, in contrast to flexible structures proposed by others , would fit the hydrodynamic data.…”
Section: Discussionmentioning
confidence: 81%